THE ORETICAL ASPECTS OF TEACHING COMMUNICATION IN ENGLISH TO HIGH SCHOOL STUDENTS USING MASS MEDIA IN VLE - Калинина, И.А.; Бежина, В.В. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2021)
Relevance. This article is devoted not only to the theoretical aspects of teaching the communication to high school students in English using the mass media, but also to the practical application of the knowledge gained. The authors consider the role of the mass media in teaching speaking, writing, reading and listening, and reveal the concept of communication, mass media and the features of distance learning. Goal: to teach the use of the mass media materials to develop communication at English lessons.
Keywords: communication; mass media; speaking; writing; reading; listening